Violence Against Migrant Filipino Women in Australia: Making Men's Behavior Visible - Saroca, Nicki (Review of Women's Studies, 2006)
This paper argues that we need to look at how men discursively construct and treat their partners to understand why violence occurs in intimate relationships between Australian men and Filipino women. Comparing the behavior of two groups of non-Filipino men in their intimate relationships with Filipino women puts the focus on men and makes their behavior visible. The men in the first group were in relationships with Filipino women who were killed or have disappeared in Australia. The men's biographies are drawn from interviews with their partner's family members and friends. The second group of men, with whom I conducted interviews and ethnographic research, are married to Filipino women. Domestic violence is a feature of some of the relationships because the two groups of men differ markedly in their constructions and treatment of their female partners. The men in the first group believed and acted in ways which suggested these women were their 'property', that they 'owned' the women, that the women did not have any rights. Exploring the dynamics of these different relationships, I demolish several myths about Filipino women and their non-Filipino partners, as well as the violence Filipino women experience. Additional narratives of Filipino women are woven through my analysis.